Calcium oxalate crystal-induced secretome derived from proximal tubular cells, not that from distal tubular cells, induces renal fibroblast activation - Chadanat Noonin; Tanakorn Itsaranawet; Visith Thongboonkerd (European Journal of Medical Research, 2023)
Abstract Background Kidney stone disease (KSD) is commonly accompanied with renal fibrosis, characterized by accumulation and reorganization of extracellular matrix (ECM). During fibrogenesis, resident renal fibroblasts are activated to become myofibroblasts that actively produce ECM. However, such fibroblast–myofibroblast differentiation in KSD remained unclear. Our present study thus examined effects of secreted products (secretome) derived from proximal (HK-2) vs. distal (MDCK) renal tubular cells exposed to calcium oxalate monohydrate (COM) crystals on activation of renal fibroblasts (BHK-21). Methods HK-2 and MDCK cells were treated with 100 µg/ml COM crystals under serum-free condition for 16 h. In parallel, the cells maintained in serum-free medium without COM treatment served as the control. Secretome derived from culture supernatant of each sample was mixed (1:1) with fresh serum-free medium and then used for BHK-21 culture for another 24 h. Results Analyses revealed that COM-treated-HK-2 secretome significantly induced proliferation, caused morphological changes, increased spindle index, and upregulated fibroblast-activation markers (F-actin, α-SMA and fibronectin) in BHK-21 cells. However, COM-treated-MDCK secretome had no significant effects on these BHK-21 parameters. Moreover, level of transforming growth factor-β1 (TGF-β1), a profibrotic factor, significantly increased in the COM-treated-HK-2 secretome but not in the COM-treated-MDCK secretome. Conclusions These data indicate, for the first time, that proximal and distal tubular epithelial cells exposed to COM crystals send different messages to resident renal fibroblasts. Only the secretome derived from proximal tubular cells, not that from the distal cells, induces renal fibroblast activation after their exposure to COM crystals. Such differential effects are partly due to TGF-β1 secretion, which is induced by COM crystals only in proximal tubular cells.